Implementasi Manajemen PNS Berbasis Sistem Merit Dalam Penempatan Jabatan Struktural Pegawai di Pemerintah Provinsi DKI Jakarta - Denny Kuswara; Ima Mayasari (Cakrawala Repositori IMWI, 2023)
The principle of "The Right Man On The Right Place" is in line with the concept of a merit system that has been formulated in the State Civil Apparatus Law. Increasing the capacity and capability of bureaucratic performance is one of the important things in Bureaucratic Reform in Indonesia. Methods that can be used to improve employee performance can be done by implementing civil servant management that pays attention to one of the issues related to employee placement. Employee placement is an organizational strategic planning because it is a policy in determining the level of effectiveness of employees and organizations in achieving goals. The formulation in this research is how to implement merit-based civil servant management in the placement of structural positions for DKI Jakarta Provincial Government employees in accordance with the qualifications, competencies and performance needed by the organization. This research aims to prepare the best scheme to ensure that the placement in structural positions for employees is in accordance with the merit system theory, which includes competence, qualifications and performance based on existing phenomena. The data was analyzed using qualitative data analysis techniques, namely descriptive phenomenological analysis. In the discussion of the research focus, the implementation of civil servant management based on 3 aspects of the merit system, namely qualifications, competencies and performance, as well as a discussion of the framework for civil servant management based on the merit system in the placement of structural positions for employees are presented. The results found that the DKI Jakarta Provincial Civil Service Agency uses the results of the Assessment Center as policy material for stakeholders to be able to reduce the mismatch between employee competency profiles and the tasks needed or to be carried out. The process of civil servant management based on the merit system begins with an analysis related to the formation needs, qualifications and competencies needed for civil servants and organizations. Then the process of mapping employee competency profiles through the Assessment Center is carried out to determine employee competence as a basis for placement. In another context, the management of civil servants based on the merit system has also been prepared and developed the concept of talent management in supporting efforts to map the 9 Boxes of talent for existing civil servants to get a picture of the competencies and profiles of civil servants that can be projected according to organizational needs.